Antiallodynic effects of KDS2010, a novel MAO-B inhibitor, via ROS-GABA inhibitory transmission in a paclitaxel-induced tactile hypersensitivity model - Su Eun Park (Molecular Brain, 2022)
Abstract Monoamine oxidase (MAO) inhibitors have been investigated for the treatment of neuropathic pain. Here, we assessed the antiallodynic effects of a novel MAO-B inhibitor, KDS2010, on paclitaxel (PTX)-induced mechanical hypersensitivity. Oral administration of KDS2010 effectively relieved PTX-induced mechanical hypersensitivity in a dose-dependent manner. KDS2010 (25 mg/Kg) significantly prevented and suppressed PTX-induced pain responses with minimal effects on the body weight, motor activity, and working memory. KDS2010 significantly reduced reactive astrocytosis and reactive oxygen species (ROS) level in the L4–L6 spinal cord of PTX-treated mice. Furthermore, KDS2010 reversed the attenuation of GABAergic spontaneous inhibitory postsynaptic current (sIPSC) frequency in spinal dorsal horn neurons, although it failed to restore the reduced tonic GABAA inhibition nor the increased GABA transporter 1 (GAT1) expression in PTX-treated mice. In addition, bath application of a reactive oxygen species (ROS) scavenger (PBN) restored the sIPSC frequency in PTX-treated mice but not in control and PTX + KDS2010-treated mice. These results indicated that the antiallodynic effect of KDS2010 is not due to a MAO-B-dependent GABA production. Finally, PBN alone also exerted a similar analgesic effect as KDS2010, but a co-treatment of PBN with KDS2010 showed no additive effect, suggesting that inhibition of MAO-B-dependent ROS production is responsible for the analgesic effect by KDS2010 on PTX-induced allodynia. Overall, KDS2010 attenuated PTX-induced pain behaviors by restoring the altered ROS level and GABAergic inhibitory signaling in the spinal cord, suggesting that KDS2010 is a promising therapeutic strategy for chemotherapy-induced peripheral neuropathy.